Identification and phylogenetic analysis of voltage-gated sodium channel haplotypes in the malaria vector Anopheles sinensis using a high-throughput amplicon sequencing approach - Ruoyao Ni; Nian Liu; Mei Li; Weiping Qian; Xinghui Qiu (Parasites & Vectors, 2021)
Abstract Background Anopheles sinensis is a dominant vector for malaria transmission in Asian countries. Voltage-gated sodium channel (VGSC) mutation-mediated knock-down resistance (kdr) has developed in many A. sinensis populations because of intensive and long-term use of pyrethroids. Our previous study showed that multiple mutations at position 1014 of the VGSC were heterogeneously distributed in A. sinensis populations across Sichuan, China. Methods To understand resistance genotypes at the haplotype level and reconstruct the phylogenetic relationship of VGSC haplotypes, a cost-effective next-generation sequencing (NGS)-based amplicon sequencing approach was established to clarify haplotypes containing codon 1014 of the VGSC gene from a total of 446 adults collected in 12 locations of Sichuan, China. Results Nineteen (19) haplotypes were identified, including 11 wild 1014L, 6 resistance 1014F, and 2 resistance 1014C haplotypes. We found that resistance haplotypes of A. sinensis VGSC were widely distributed at frequencies ranging from 3.67 to 92.61%. The frequencies of the 1014C haplotype in the southeast of Sichuan (Luzhou, Guangan, and Suining) were relatively higher than those in other sampling locations. Phylogenetic analyses support that kdr-type mutation at position 1014 is not singly originated and resistance 1014C haplotypes evolve from TTT-encoding 1014F. Conclusions A cost-effective next-generation sequencing (NGS)-based amplicon sequencing approach has been established in this study. The data revealed the patchy distribution of VGSC resistance haplotypes with overall high frequencies in Sichuan, China. Phylogenetic analyses support multiple origins and sequential evolution (1014L → 1014F → 1014C) for kdr-type mutations in A. sinensis. Graphical abstract